Synthesis and Characterization of Chitosan-graft-Poly (N-Allyl Maleamic Acid) Hydrogel Membrane - Saber-Samandari, Samaneh; Gazi, Mustafa; Yilmaz, Osman (Springer, 2013)
A chitosan-graft-poly(N-allyl maleamic acid) hydrogel membrane was prepared by radical polymerization in the absence of a cross-linker. The product was characterized by Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), and scanning electron microscopy (SEM) to confirm the formation of hydrogels. Transparent hydrogels have been observed to exhibit as much as 223.4 % swelling capacity, following pseudo-second-order kinetic models. The synthesized hydrogel membrane was subsequently utilized for removal of copper ions from an aqueous solution in the presence of several different functional groups. The effects on adsorption efficiency of various parameters such as time, temperature, pH, initial concentration of copper (II) solution, and amount of hydrogel were also investigated. The maximum adsorption capacity and efficiency were found to be 50.75 mg g(-1) and 99.91 %, respectively, by the 0.004 mg adsorbent after 12 h of immersion in copper solution. Finally, the result showed that hydrogel membrane is pH sensitive to copper (II) adsorption and has maximum adsorption efficiency near to the pH of ground water.
Keywords: Chitosan; Membrane; Copper removal; Water treatment